Transforming the future of infrastructure through smarter information : proceedings of the International Conference on Smart Infrastructure and Construction, 27-29 June 2016 - Mair, R. J.; Soga, Kenichi; Jin, Y.; Parlikad, Ajith; Schooling, J. M. (ICE Publishing, 2016)
The International Conference on Smart Infrastructure and Construction (ICSIC) brings together world-leading academics and practitioners from the fields of infrastructure planning, asset management and sensing.